2017
DOI: 10.1111/eff.12387
|View full text |Cite
|
Sign up to set email alerts
|

Dietary niche expansion and niche shift in native marble trout (Salmo marmoratus) living in sympatry with introduced rainbow trout (Oncorhynchus mykiss)

Abstract: The non-native rainbow trout (Oncorhynchus mykiss) has been introduced worldwide for angling purposes and has established self-reproducing populations in many parts of the world. Introduced rainbow trout often have negative effects on the native salmonid species, ranging from decrease abundance, growth and survival, to their local extinction. Assessing the effects of introduced rainbow trout on the native species is thus crucial to better set up conservation programmes. In this study, we investigated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 91 publications
(119 reference statements)
1
11
0
Order By: Relevance
“…shows that larger trout have higher trophic positions compared to smaller ones, which is consistent with previous findings on the trophic ecology of marble trout (Musseau et al, 2015(Musseau et al, , 2018 and fish trophic ecology in general (Smith & Reay, 1991). High trophic positions in marble trout populations are caused by a sizeable proportion of fish prey in predators' diet (Musseau et al, 2018). The marble populations investigated in the present study are living in allopatry, therefore, the higher trophic positions are due to cannibalism, which has been directly observed several times during sampling campaigns (A. J.…”
Section: The Very Low Variability In Between-individual Effects Over supporting
confidence: 92%
“…shows that larger trout have higher trophic positions compared to smaller ones, which is consistent with previous findings on the trophic ecology of marble trout (Musseau et al, 2015(Musseau et al, , 2018 and fish trophic ecology in general (Smith & Reay, 1991). High trophic positions in marble trout populations are caused by a sizeable proportion of fish prey in predators' diet (Musseau et al, 2018). The marble populations investigated in the present study are living in allopatry, therefore, the higher trophic positions are due to cannibalism, which has been directly observed several times during sampling campaigns (A. J.…”
Section: The Very Low Variability In Between-individual Effects Over supporting
confidence: 92%
“…Although rainbow trout is known to take food from other Salmonids, the niche shift of marble trout when occurring in sympatry with rainbow trout in Lower Idrijca was not caused by a niche replacement of marble trout by rainbow trout. Musseau et al () also found that marble trout in Upper and Lower Idrijca occupy a high trophic position (3.5 in Upper to 3.9 in Lower Idrijca), which confirms observations of piscivory and cannibalism in other marble trout populations. Marble trout in Lower Idrijca showed higher δ 13 C than marble trout in Upper Idrijca, which is likely to be caused by the inclusion of rainbow trout as additional prey in the diet of marble trout (Musseau et al, ).…”
Section: Introductionmentioning
confidence: 57%
“…Musseau et al () also found that marble trout in Upper and Lower Idrijca occupy a high trophic position (3.5 in Upper to 3.9 in Lower Idrijca), which confirms observations of piscivory and cannibalism in other marble trout populations. Marble trout in Lower Idrijca showed higher δ 13 C than marble trout in Upper Idrijca, which is likely to be caused by the inclusion of rainbow trout as additional prey in the diet of marble trout (Musseau et al, ). Marble and rainbow trout living in sympatry are thus competitors for food and space, and we expect effects of this inter‐specific competition on vital rates, life histories and population dynamics of marble trout living in sympatry with rainbow trout, such as faster growth, earlier reproduction, lower survival and lower population densities in marble trout living in Lower Idrijca (sympatry) than in Upper Idrijca (allopatry).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…The most substantial evidence of this kind has been produced for the alpine streams of the Rhine and Lake Constance, where large increases in the range and abundance of rainbow trout in recent decades coincided with the decline or collapse of several native brown trout populations (Bassi et al, ; Burkhardt‐Holm, Peter, & Segner, ). There remains a minority of studies that have indicated weak or negligible impacts of rainbow trout on native fishes (Musseau et al, , ; Vincenzi, Crivelli, Jesenšek, & De Leo, ).…”
Section: Introductionmentioning
confidence: 99%